2020
DOI: 10.2147/cmar.s260129
|View full text |Cite
|
Sign up to set email alerts
|

<p>Curcumin Modifies Epithelial–Mesenchymal Transition in Colorectal Cancer Through Regulation of miR-200c/EPM5</p>

Abstract: Background: The serious side effect of current conventional treatments for patients with metastatic colorectal cancer (CRC) highlights the requirement of an alternative treatment strategy. Natural compounds, such as curcumin, have been gained much attention due to its low toxicity and anti-tumor effect. Methods: qPCR and Western blot were used to measure the molecular changes induced by curcumin. Wound-healing assay and transwell assay were conducted to study the effect on cell migration and invasion. RT 1 PCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…These observations indicated that curcumin inhibited EMT by upregulating miR-301a-3p expression. It has been reported that curcumin suppressed EMT through the miR-200c/EPM5 axis and the ERK5/AP-1 and TET1-NKD-Wnt signaling pathways ( 60-62 ). Furthermore, our results indicated that the targeting of STAT3 by miR-301a-3p and the overexpression of STAT3 also reversed the inhibitory effects of curcumin on EMT in TPC-1 cells.…”
Section: Discussionmentioning
confidence: 99%
“…These observations indicated that curcumin inhibited EMT by upregulating miR-301a-3p expression. It has been reported that curcumin suppressed EMT through the miR-200c/EPM5 axis and the ERK5/AP-1 and TET1-NKD-Wnt signaling pathways ( 60-62 ). Furthermore, our results indicated that the targeting of STAT3 by miR-301a-3p and the overexpression of STAT3 also reversed the inhibitory effects of curcumin on EMT in TPC-1 cells.…”
Section: Discussionmentioning
confidence: 99%
“…e high degree of malignancy, rapid development, poor prognosis, and chemoradiotherapy resistance of CRC often lead to the failure of treatment. Previous studies have shown that curcumin is a promising candidate for the treatment of CRC [15][16][17][18][19]. However, the regulatory mechanism of curcumin in CRC treatment has not been systematically elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent in vivo experiments confirmed that curcumin can reduce inflammation and CRC formation in mouse models [17]. Upregulation of miR-200c and downregulation of EPM5 can inhibit EMT in CRC to prevent or delay the progression of CRC [18]. It can also block G2/M and G1 cycles to inhibit cell growth and induce apoptosis of colorectal cancer cells [19].…”
Section: Introductionmentioning
confidence: 88%
“…Further study displayed that miR-200c could directly target EPM5, and decreased EPM5 could contribute to curcumin-induced inhibition on EMT progression. Moreover, high expression of EPM5 was positively correlated with advanced TNM stages and poor survival in CRC patients [ 105 ]. Curcumin had anti-tumor effects and could up-regulate the expression of miR-206 in CRC cells.…”
Section: Compounds Regulated Mirnas As Potential Therapeutics For Inhibiting Emtmentioning
confidence: 99%